AUTHENTIC MATERIALS IN EXTENSIVE READING CLASS AT STAIN PONOROGO - Dhinuk Puspita Kirana (IAIN PONOROGO, 2013)
It is widely believed that English Foreign Language (EFL) learners need to develop their language proficiency by getting so much input. Moreover, students need to be familiarized with the real English usage where real forms of communication and cultural knowledge are crucially exposed. Teaching through authentic materials will make the learners feel that they are learning a real language which is used by the real native speakers for real communication. incorporating authentic materials helps students acquire an effective communicative competence in the language focus. The research intended to describe the implementation of authentic materials in extensive reading class, the problems arise and the students’ responses toward the authentic materials in extensive reading class. The design of the research was Descriptive Qualitative method and the research subject was the lecturer of Extensive Reading class and 33 students in B class of the fourth semester of STAIN Ponorogo who took Extensive Reading subject. The instruments used were in the form of observation sheet, interview guideline and questionnaire. The implementation of authentic materials in extensive reading class covered some procedures into three main phases namely (1) Pre Activity, (2) Main Activity and (3) PostActivity. The activities in main activity are as follows: (a) Pre Activity; (b) Whilst Activity; and (3) The language focus stage. There were problems arose during the implementation in terms of complicated planning, more time allocation and some disinterested students. Finally, the students showed significantly positive attitude toward the implementation of authentic materials in extensive reading class.